Redefining ASEAN Way: Assesing Normative Foundation on Inter-governmental Relationship in Southeast Asia - M. Faishal Aminuddin; Joko Purnomo (JAS (Journal of ASEAN Studies), 2017)
Abstract This paper endeavors to review the inter-state relation in Southeast Asia countries. Especially in government policy. The most significant problem in regional relationship is about the absence of political awareness. As a consequence, ASEAN only provides limited positive achievement in political performance regionally. This article provides an alternative explanation for the limited achievement in political performance of ASEAN by assessing the implication of using non-interference principe to the incidence of ignorance and disconnection between ASEAN countries that leads to lack of political awareness. In this paper, we try to propose a combination between formal diplomacy actions done by state institution  and informal diplomacy actions done by non-government actors. We also points out an alternative strategy to promote political awareness on the future of SEA community. First, open policy to connecting diplomatic based community. Second, optimalize the regional cooperation with more concern with democracy and human rights issue. Third, building and institutionalizing political awareness through people participation. Keywords: regional cooperation, non-interference principal, political awareness, comunitarian